Qualimetric Approach in Determining the Investment Attractiveness of a Ukrainian Railway Entity - V.Bormotova, M.; D.Bronza, S.; V.Mashoshyna, T.; M.Troinikova, O. (International Journal of Engineering and Technology, 2018)
Investment is one of the critical tools to enable an economic recovery from the economic crisis and encourage the progressive development of any country. The main issue that prevents any industry from growing is shortage of funding. And that’s exactly why assessment of investment attractiveness of any project (country, industry, region, or company) is highly important. Based on the study of the existing views on the definition of the concept of investment attractiveness in literary sources, these views have been grouped by the main essential feature used for the definitions.The article presents an analysis of the investment attractiveness of Ukraine; articulates and systematizes the concept of investment attractiveness; suggests a definition of the concept in terms of qualimetry; examines the special aspects of investments in the transport industry (in particular, the railroad industry); and suggests a qualimetric model that enables the most adequate and essential assessment of the investment attractiveness of a railroad entity, based on the external and internal factors, and both qualitative and quantitative characteristics.